Adoption of Web 3.0: Factors Affecting Behavioral Intention - Lubna Khan; Syed Fatehyab Mehdi; Noman Ahsan (Journal of Management Practices, Humanities and Social Sciences, 2023)
In the present study, we explore the landscape of web 3.0 technology, a pivotal phase in the digital domain. Multiple factors have been identified that influence the behavioral intention of the users and further the adoption of web 3.0 technology. By employing a deductive approach, we collected 200 samples from the IT professionals. To draw the sample, non-probability purposive sampling techniques were used. The PLS-SEM technique was used to predict the causal relationship between the studied variables, as it has the ability to provide meaningful results for complex models with a minimal sample. Results revealed the factors that are influencing the behavioral intention of the users. Among others, digital dexterity plays a crucial role in affecting the behavioral intention of Web 3.0 technology users. In addition, the electronic word of mouth also plays an important in enhancing the behavioral intention of the users which further enhances the adoption of web 3.0 technology. Data privacy security and perceived ease of use both have a positive and significant impact on the user's behavioral intention. Interestingly, performance expectancy was found to be an insignificant element that increases user intention. These findings serve as valuable resources for developers and marketers, allowing them to leverage their potential for strengthening user privacy and data security